PENDIDIKAN ISLAM: PROSES PENDIDIKAN YANG MEMANUSIAKAN MANUSIA - Abdul Manan (Al Hikmah: Jurnal Studi Keislaman, 2012)
Education is a process of delivering value to a very broad scope. Education is how people can carry out life and living. Education is an attempt to develop the potential of the base (fitrah), so the man called the pedagogic creature that can be educated as well as having the ability to carry out educational activities. As a process, education has a role to transform the knowledge and values on others. Because humans act both as subject and object in education, then the process was planned and used to develop, cultivate and direct the basic human potential, to grow and develop and properly directed. In this case the size should be in the teaching of religion is a human being who covers aspects (dimensions) ukhrowi, emotional, social, intellectual and physical. This is the real man, so that education is the process of humanizing mankind.